Effects of magnetic field, binary particle loading and rotational conic surface on phase change process in a PCM filled cylinder - Ghachem, Kaouther; Selimefendigil, Fatih; Öztop, Hakan Fehmi; Almeshaal, Mohammed; Alhadri, Muapper; Kolsi, Lioua (Elsevier, 2021)
In the present work, coupled effects of forced convection, rotational conic surface and magnetic field on the phase change dynamics are numerically explored by using finite element method for a phase change material (PCM) filled 3D cylindrical reactor. The PCM filled region has a conic shape and it is rotating. The study is conducted for various values of rotational Re number (between 0 and 2500), magnetic field strength (Hartmann number between 0 and 30) and conic surface aspect ratio (between 1 and 2). It is observed that the coupled interactions between the rotational surface and magnetic field significantly affect the phase change process dynamics and convective heat transfer between different phases. Optimum value of rotational Reynolds number for minimum complete phase transition time is achieved at Rew = 1000. The magnetic field has a positive impact on the phase change process while it is impact is profound without surface rotation. There are 98% and 65% reductions in the complete phase transition times when configurations at Rew = 1000 are compared with motionless conic surface case in the absence and presence of magnetic field. The effects of rotation are profound when different aspect ratios of the PCM filled region is considered. The transition time is increased up to 553% without rotation while this value is only 86% when cases with lowest and highest aspect ratio are compared. A modal analysis with 30 mode is used to capture the phase change dynamics and coupled interactions between the rotational surface and magnetic field on the variation of liquid fraction.
Keywords: Magnetic field; Rotating conic surface; Phase change dynamics; CFD; Modal analysis; Nanofluid